Socio-Islamic training indications according to philosophy of intercultural basics in social studies books during elementary school in Iran - Fahimeh Nasiri; Tayebeh Mahrouzadeh; Maryam Banahan (Religion & Communication)
This study has been implemented to clarify Socio-Islamic Training indications according to philosophy of intercultural basics in social studies books during elementary school in Iran. The mentioned study is practical due to nature, qualification and target. Descriptive method and theoretical principal analysis and interview with well-known experts of philosophy have been utilized to extract intercultural philosophy principal. Semi- structured interview was the method to gather data in this section. Because of that, intended experts of intercultural philosophy that is, six theoreticians, were selected who own a book or an essay. Analysis- inferential method was used to answer training indication questions. The Findings shows that intercultural philosophy principles include two components on ontology such as evolved structure and existence pluralistic; the meaning of life pluralistic in epistemology includes four components; distributed truth, self–analysis and analysis of other, understandings by conversation due to reasoning and also having pluralistic nature. Beside that Anthropology principal consists of four components too; adherence of human to nature, socialized human being, having freedom and social responsibility, innate possessing of thought and philosophy by human and eventually, in analysis of merit there are four components; possessing relativity nature, possessing pluralistic nature, possessing anti-capitalism nature and having aesthetics nature. Principals of Intercultural philosophy is confirmed by Islam includes eight bases for human, such as being socialized, social responsibility, justice, anti-capitalism, tolerance, intellectualism, mutual understanding and converse in way that training indication has been extracted in three areas including goals, basics and methods.